Invention d’un nouvel espace public : la collaboration entre Isamu Noguchi et Gordon Bunshaft - Hiromi Matsugi (In Situ)
This paper deals with the cooperation that the sculptor Isamu Noguchi and the architect Gordon Bunshaft established in the United States for two decades, following World War II. In spite of the unfavourable context at that time, they worked on several projects that contributed to a renewal of the concept of public space, anticipating the change in urban legislation and the renewal of public art which started at the end of the 1960s. The analysis of three projects – Lever House courtyard (New York, 1951-1953), Chase Manhattan plaza (New York, 1956-1964) and the garden of the Beinecke Library (Yale University, 1960-1963) – allows us to understand how two creators took advantage of a potential obstacle to achieve their projects, and appreciate an artistic work in the context of a close collaboration.